C/EBPβ Regulates HIF-1α-Driven Invasion of Non-Small-Cell Lung Cancer Cells - Seung Hee Seo; Ji Hae Lee; Eun Kyung Choi; Seung Bae Rho; Kyungsil Yoon (Biomolecules)
Metastatic cancer accounts for most cancer-related deaths, and identifying specific molecular targets that contribute to metastatic progression is crucial for the development of effective treatments. Hypoxia, a feature of solid tumors, plays a role in cancer progression by inducing resistance to therapy and accelerating metastasis. Here, we report that CCAAT/enhancer-binding protein beta (C/EBPβ) transcriptionally regulates hypoxia-inducible factor 1 subunit alpha (HIF1A) and thus promotes migration and invasion of non-small-cell lung cancer (NSCLC) cells under hypoxic conditions. Our results show that knockdown or forced expression of C/EBPβ was correlated with HIF-1α expression and that C/EBPβ directly bound to the promoter region of HIF1A. Silencing HIF1A inhibited the enhanced migration and invasion induced by C/EBPβ overexpression in NSCLC cells under hypoxia. Expression of the HIF-1α target gene, SLC2A1, was also altered in a C/EBPβ-dependent manner, and knockdown of SLC2A1 reduced migration and invasion enhanced by C/EBPβ overexpression. These results indicate that C/EBPβ is a critical regulator for the invasion of NSCLC cells in the hypoxic tumor microenvironment. Collectively, the C/EBPβ-HIF-1α-GLUT1 axis represents a potential therapeutic target for preventing metastatic progression of NSCLC and improving patient outcomes.